Dynamic analysis of NGO emergency relief goods supply: 2020 Hubei COVID-19 as a case - Yi Lu; Yi Lu; Yuhang Wang (Frontiers Media S.A., 2023)
IntentionGlobal emergencies cause significant damage to lives, assets, and the economy. Therefore, the supply of relief goods is essential in emergency relief contexts, which is generally the function of non-government organizations (NGOs) as they have unique relief goods supply advantages. However, few studies have explored the influencing factors on NGO relief goods supply efficiency. To systematically explore the factors affecting supply efficiency, we aim to develop a supply chain model for simulating and providing policy suggestions.MethodTaking the 2020 Hubei COVID-19 as case study, this research developed a system dynamic (SD) model for the NGO relief supply system to evaluate and quantify the impact of factor changes on relief supplies.ConclusionIt was found that transportation and information delays aggravated the NGO emergency supply chain bullwhip effect and caused large supply fluctuations. The initial relief goods inventory was found to be a decisive factor in reducing shortages in disaster areas; however, government support was found to play only a limited role in reducing information and transportation delays.ValueThis study enriches NGO emergency supply chain literature and provides suggestions for guiding NGO relief goods supplies in the future.